Harnessing FOXP3+ regulatory T cells for transplantation tolerance. - Waldmann, H; Hilbrands, R; Howie, D; Cobbold, S (American Society for Clinical Investigation, 2014)
Early demonstrations that mice could be tolerized to transplanted tissues with short courses of immunosuppressive therapy and that with regard to tolerance to self, CD4+FOXP3+ regulatory T cells (Tregs) appeared to play a critical role, have catalyzed strategies to harness FOXP3-dependent processes to control rejection in human transplantation. This review seeks to examine the scientific underpinning for this new approach to finesse immunosuppression.